Perfringolysin O as a useful tool to study human sperm physiology - Pocognoni, Cristián Adrián (2013)
Objective: To evaluate perfringolysin O, a cholesterol-dependent pore-forming cytolysin, as a tool to study several aspects of human sperm physiology. Design: Prospective study. Setting: Basic research laboratory. Patient(s): Human semen samples with normal parameters obtained from healthy donors. Intervention(s): Interaction of recombinant perfringolysin O with human spermatozoa. Main Outcome Measure(s): Assessment of perfringolysin O binding to spermatozoa, tests for acrosome and plasma membrane integrity, and acrosomal exocytosis assays. Result(s): Perfringolysin O associated with human spermatozoa at 4 C. The binding was sensitive to changes in cholesterol concentrations and distribution occurring in the plasma membrane of these cells during capacitation. When perfringolysin O–treated sperm were incubated at 37 C, the plasma membrane became permeable, whereas the acrosome membrane remained intact. Permeabilized spermatozoa were able to respond to exocytic stimuli. The process was inhibited by proteins that interfere with membrane fusion, indicating that large molecules, including antibodies, were able to permeate into the spermatozoa. Conclusion(s): PFO is a useful probe to assess changes in the amount and distribution of the active sterol fraction present in the sperm plasma membrane. The toxin can be used for the efficient and selective permeabilization of this membrane, rendering a flexible experimental model suitable for studying molecular processes occurring in the sperm cytoplasm. (Fertil Steril 2013;99:99–106. 2013 by American Society for Reproductive Medicine).